Huáng Jīn Zhī Luàn and Political Stability in The Three Kingdoms Literature - Kumyodchai, Pramahajakrapong; Na Ayuttaya, Fongjan Suksawat (Journal of Thammawat, 2022)
Huáng Jīn Zhī Luàn Was a large rebellion in the late Eastern Han dynasty, where the forces formed by the union of people. There are 2 important factors: 1) the court has corruption 2) the economic downturn at the utmost. This group of rebels has deteriorated confidence in the court and the army. This event was the start of the horrible political stability of the Han Dynasty. And finally collapsed. Huáng Jīn Zhī Luàn conveyed to politics in Thailand that the government will be stable political stability. Must have a system to prevent corruption, which creates confidence for the people in helping to develop the country and will have to look after the people in the economy, both at the micro and macro levels, for the well-being of the people.